No-Show to Primary Care Appointments: Why Patients Do Not Come. (October 2013) - Kaplan-Lewis, Emma; Percac-Lima, Sanja
Background: Missed primary care appointments lead to poor disease control and later presentation to care. No-show rates are higher in clinics caring for underserved populations and may contribute to poorer health outcomes in this group. The objective of this study was to determine who were the patients not showing to primary care appointments and their reasons to no-show.Methods: A retrospective study was conducted at a community health center serving a predominantly Latino, immigrant, low-income population. Adult patients >18 years old who did not show to primary care appointments during a 5-month period were called by a bilingual (English and Spanish) patient service coordinator. The patients' reported reason for missing the appointment was documented. Two-sided t test of proportions was used to compare demographic characteristics of the patients that showed to their appointments to patients that did not.Results: Of 7508 scheduled appointments, 5604 were included in the analysis and 927 (16.5%) no-showed. There were 735 (79%) calls made to the patients who missed their appointments and 273 (37%) were reached. The 2 most common reasons for missing an appointment were forgetting (n = 97, 35.5%) and miscommunication (n = 86, 31.5%). When compared with patients who came to their appointments, patients who no-showed were younger ( P < .0001), more likely to be black ( P = .0423) or Hispanic ( P = .0001), and to have Medicaid ( P < .0001).Conclusions: No-show rates interfere with quality primary care. Interventions designed to target reasons for no-show are needed to help reduce the no-show rate, improve access and decrease health disparities in underserved patient populations.